2012
DOI: 10.1021/am300425x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Lignin Polyurethane Properties with Lewis Acid Treatment

Abstract: Chemical modification strategies to improve the mechanical properties of lignin-based polyurethanes are presented. We hypothesized that treatment of lignin with Lewis acids would increase the concentration of hydroxyl groups available to react with diisocyanate monomers. Under the conditions used, hydrogen bromide-catalyzed modification resulted in a 28% increase in hydroxyl group content. Associated increases in hydrophilicity of solvent-cast thin films were also recorded as evidenced by decreases in water co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 53 publications
6
152
1
Order By: Relevance
“…This may be due to part cleavage of ether bonds during the demethylation process [18]. The results showed that the WSAL was demethylated successfully and more efficiently than in other reported methods [21,25]. The methods reported in the past, employed demethylation processes with harsher conditions and had a lower yield of phenolic hydroxyl groups.…”
Section: Characterization Of Demethylated Ligninmentioning
confidence: 90%
See 1 more Smart Citation
“…This may be due to part cleavage of ether bonds during the demethylation process [18]. The results showed that the WSAL was demethylated successfully and more efficiently than in other reported methods [21,25]. The methods reported in the past, employed demethylation processes with harsher conditions and had a lower yield of phenolic hydroxyl groups.…”
Section: Characterization Of Demethylated Ligninmentioning
confidence: 90%
“…Lignin has many methoxyl groups and it has been shown that lignin can also be demethylated using a Lewis acid [23,24]. Furthermore, Chung and Washburn [25] reported demethylation of softwood kraft lignin (SKL) by hydrobromic acid and phase transfer catalyst hexadecyltri-n-butylphosphonium bromide (TBHDPB) in a H 2 O-DMF mixture. The hydroxyl group in SKL increased by 28% and the demethylated SKL was more reactive than the unmodified SKL when used for polyurethane preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of isocyanates used such as toluene-2,4-diisocyanate, isophorone diisocyanate, and 4,4-methylene diphenyl diisocyanate are aromatic in structure while aliphatic isocyanates, such as hexamethylene diisocyanate (HMDI), are also used (Teo et al, 1997, Chan-Chan et al, 2010, Prisacariu, 2011, Chung and Washburn, 2012, Zhang et al, 2015. Polyols are usually the more flexible of the two components which allows the formation of flexible PU materials and usually consist of polyesters, polyethers, or glycols such as polyethylene glycol (PEG), 1,4-butanediol, and polypropylene glycol (PPG) (Grassie and Zulfiqar, 1978;Wen et al, 2001;Oprea, 2010;Nozaki et al, 2017).…”
Section: Polyurethane (Pu)mentioning
confidence: 99%
“…Hydroxyl group content is best determined after acetylation of hydroxyl groups by acetic anhydride in the presence of pyridine. 33,34 The acetoxy groups produced in this reaction correspond to hydroxyl groups of lignin and appear at chemical shifts of approximately 2 ppm. 34,35 After acetylation, the phenolic hydroxyl group can be determined selectively by relatively fast, selective, deacetylation of phenolic acetyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 The acetoxy groups produced in this reaction correspond to hydroxyl groups of lignin and appear at chemical shifts of approximately 2 ppm. 34,35 After acetylation, the phenolic hydroxyl group can be determined selectively by relatively fast, selective, deacetylation of phenolic acetyl groups. 36 Alkylation of hydroxyl group was performed to determine hydroxyl groups in 1 H NMR spectra.…”
Section: Introductionmentioning
confidence: 99%